The Effect of Financial Performance on Stock Prices in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange 2017-2021 Period - Aqsal Satya Happrabu; Ariyani (Jurnal Ekonomi, 2022)
This study aims to determine and analyze the effect of financial performance through return on assets , return on equity, net profit margin, and earnings per share either simultaneously or partially on stock prices. food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population of this study is all food and beverage sub-sector companies indexed on the IDX for the 2017-2021 period. The sampling technique used purposive sampling which resulted in 17 sample companies. Data analysis used multiple linear regression. The results of this study indicate that simultaneously stock prices are significantly influenced by financial performance through return on assets (ROA), return on equity (ROE), net profit margin . (NPM), and earnings per share (EPS). Return on assets (ROA) and earnings per share (EPS) have a significant effect on stock prices , while return on equity (ROE) and net profit margin (NPM) have no significant effect on stock prices. The implication of the results of this study is that companies increase their income and assets so that net income is greater and earnings per share are also greater. Shareholders should not immediately withdraw their shares when the share price declines in the hope that their financial performance is stable.